Challenges in wide implementation of genome editing for crop improvement - Jung, J.H.; Seo, Y.W. (Korean Society of Crop Science, 2017)
Genome editing technologies using customizable sequence specific nucleases (SSNs) enables precise genome modification in plants, which has revolutionized functional genomics research as well as crop improvement. Applicability of SSN-mediated genome editing ranges from targeted gene knockout and single base modification to multiple gene stacking into desired genomic sites. However, there are still considerable challenges in implementing genome editing technologies for practical crop improvement. Here, we briefly discuss the technological challenges, especially those associated with the delivery of SSNs and with homologous recombination-mediated genome editing, and address some promising solutions to overcome the issues. ？ 2017, Korean Society of Crop Science and Springer Science+Business Media B.V.